Strategi Public Realations Terkait Penggunaan Influencer Instagram Dalam Meningkatkan Brand Awareness Brand Skincare Lokal Scarlett - Mirta Ria Zai; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The rapid advancement of information and communication technology in recent decades has had a significant impact on various aspects of human life, particularly in marketing communication strategies. One of the most affected fields is public relations (PR), which has undergone major changes in methods and approaches to building relationships between organizations and their publics. Whereas PR activities once relied heavily on traditional media such as newspapers, magazines, or press conferences, digital technology has now revolutionized these practices. This study aims to explore and analyze the public relations strategies implemented by the local skincare brand Scarlett in utilizing Instagram influencers as a communication medium to enhance brand awareness. Amidst the increasingly competitive beauty industry, social media has become a strategic channel for companies to establish effective, interactive, and audience-oriented communication. As a local brand, Scarlett has successfully optimized the power of digital media by collaborating with influencers to deliver brand messages in a more personal and authentic manner. The research employed a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The findings reveal that Scarlett’s PR strategy focuses on long-term collaboration with influencers aligned with its brand image, the use of engaging visual content, and the delivery of consistent and relatable messages. This strategy has proven effective in fostering emotional connections between the brand and consumers, strengthening public trust, and reinforcing brand positioning in the local skincare market. Furthermore, the study highlights that the use of influencers as part of public relations strategies can generate a positive impact on shaping public perception and fostering consumer loyalty in the digital era.